Exploiting Bluetooth for deploying indoor LBS over a localisation infrastructure independent architecture. (22nd December 2009) - Zafeiropoulos, Anastasios; Papaioannou, Ioannis; Solidakis, Emmanuel; Konstantinou, Nikolaos; Stathopoulos, Panagiotis; Mitrou, Nikolas
This paper presents an evaluation of using the low cost Bluetooth wireless technology, as a localisation technique, fitted in a lightweight approach for providing web-based location aware content through Java enabled handheld devices. This approach separates the positioning system from the content access mechanisms, while being generic and independent to the selection of the localisation technique, i.e., GPS, Bluetooth, etc. A test case application for Bluetooth enabled smart phones demonstrates the capacity of the approach, when combined with Bluetooth localisation, to provide location based content retrieval to the widest possible array of end users, while using their personal mobile devices, without the need to acquire and manage specially built user terminals. Useful results are also extracted for Bluetooth's behaviour, while being used as a localisation technique, with regard to the provided accuracy, usual inquiry time, possible interference from other wireless technologies and imposed hardware requirements.